GEOLOGICAL FACTORS OF INFLUENCE ON STRAIN-DEFORMED STATE OF SYSTEM GEOLOGICAL ENVIRONMENT-PIPELINE IN CRYOLITHOZONE - IVANIK, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The geological factors for estimation of strain-deformed state of the system "geological environment-pipeline" in cryolithozone are analyzed. It is necessary to develop geological models on the base of geological and mathematical target setting of the continuum mechanics for safe operation of trans pipelines.